Integrated Copy-Paste Checking: Design and Services - Kulathuramaiyer, Narayanan; Bilal, Zaka; Helic, Denis (Faculty of Computer Science and Information Technology, 2008)
The advances in technology have made academic cheating far too easy for learners. Furthermore, the World-Wide-Web has brought about a widespread culture of easy-access to all sorts of information, thus reducing the need for learners to perform diligent research or study. E-learning systems would then need to incorporate the monitoring and checking for student expressions of reading and writing, while guiding them towards learning the rightful skills. This paper describes the architecture and design of an ...